INSTALLATION FOR PRELIMINARY HEATING OF THE MATERIAL BEFORE DRYING - Rasuljon Tojiyev; Azimjon Abdurayimov (European Science Publishing, 2023)
At present, methods for drying dispersed materials in variable modes have been widely used, when not only the temperature and speed of the drying agent change over time, but also the state of the material layer undergoes changes due to controlled hydrodynamics in the working volume of the drying plant. Variable modes are used for drying in oscillating modes with stepped hydrodynamic and temperature modes, as well as for drying in an isothermal cycle. If oscillating drying with alternating zones of heating and cooling of the material and drying of the material in step modes is primarily aimed at maintaining the quality of the target product, then isothermal drying consists in preheating the material to the maximum allowable temperature during subsequent drying without reducing it during the entire process with maximum dehumidification rate.
Keywords: drying, material, energy, leading to cracking.